Potential of virtual reality implementation in new era construction / Noraidawati Jaffar ... [et al.] - Jaffar, Noraidawati; Rusli, Muhammad Ammar Hazim; Ab.Wahid, Abdul Muhaimin; Syed Jamalulil, Syarifah Nur Nazihah; Shuib, Mohammad Nasharudine (2022)
Construction management software is among the latest trends in the new era of construction. Virtual Reality (VR) is largely used in the healthcare industry and the gaming sector is now considered as one of the fresh and new software introduced in the construction industry. Many construction companies are slowly learning the importance of its implementation to cope with the current trend. VR is such an immersive and interactive visualization in the process of design, engineering, construction, and management. Its advanced capabilities facilitate the interpretation of drawings produced by civil engineers and architects. It is found to be beneficial to the industry. Hence, the objective of this paper is to gain an in-depth understanding on the potential of VR implementation in construction practices. A questionnaire survey was distributed to the contractors’ companies and data was analysed statistically. The findings of the study found that VR contributes a good potential in increasing the client’s satisfaction, improving the quality of construction project as well as enhancing the safety for training. This study contributes to the body of knowledge in identifying the potential of VR technology in terms of promoting VR implementation for the construction industry.